2014
DOI: 10.1115/1.4026975
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of Cavity and Core Flow Interactions With Application to Ultra-Compact Combustors

Abstract: Reducing the weight and decreasing pressure losses of aviation gas turbine engines improves the thrust-to-weight ratio and improves efficiency. In ultra-compact combustors (UCC), engine length is reduced and pressure losses are decreased by merging a combustor with adjacent components using a systems engineering approach. High-pressure turbine inlet vanes can be placed in a combustor to form a UCC. In this work, experiments were performed to understand the performance and associated physics within a UCC. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…3(a)], where inlet air is divided into discrete air passages to allow sufficient core air diffusion and distribution while providing a transport mechanism for cavity products flowing into the core region. Further details of this front-end design can be found in Blunck et al 6 A variant of this design [CDF-2, shown in Fig. 3(b)] was examined in the first study.…”
Section: Experimental Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…3(a)], where inlet air is divided into discrete air passages to allow sufficient core air diffusion and distribution while providing a transport mechanism for cavity products flowing into the core region. Further details of this front-end design can be found in Blunck et al 6 A variant of this design [CDF-2, shown in Fig. 3(b)] was examined in the first study.…”
Section: Experimental Approachmentioning
confidence: 99%
“…A similar UCC sector has been reported previously. 6,33 A brief description of the UCC sector is provided below. Figure 2 shows a top-down view of the planar section of a UCC that displays flow elements and directions.…”
Section: Experimental Approachmentioning
confidence: 99%
See 3 more Smart Citations